2004
DOI: 10.1111/j.1365-2958.2004.04052.x
|View full text |Cite
|
Sign up to set email alerts
|

New Listeria monocytogenes prfA* mutants, transcriptional properties of PrfA* proteins and structure–function of the virulence regulator PrfA

Abstract: SummaryPrfA, a transcription factor structurally related to Crp/ Fnr, activates Listeria monocytogenes virulence genes during intracellular infection. We report two new PrfA* mutations causing the constitutive overexpression of the PrfA regulon. Leu-140Phe lies in a a a a D adjacent to the DNA-binding motif in the C-terminal domain, like a previously characterized PrfA* mutation (Gly-145Ser). Ile-45Ser, in contrast, maps to the N-terminal b b b b -roll, a structure similar to that of the Crp cAMP binding site.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 44 publications
(119 reference statements)
4
103
0
Order By: Relevance
“…Small-molecule cofactors regulate the protein activity state of many family members (19,39). While no such cofactor has been identified yet for PrfA, a variety of point mutations in prfA (prfA* mutants) that result in variant PrfA proteins whose function is locked in the intracellular activity state support the theory that PrfA activity is allosterically regulated (16,28,37,40,44,47). These prfA* mu-tants constitutively express levels of the actin-nucleating protein ActA comparable to those observed when bacteria are in the host cytosol (40).…”
mentioning
confidence: 87%
“…Small-molecule cofactors regulate the protein activity state of many family members (19,39). While no such cofactor has been identified yet for PrfA, a variety of point mutations in prfA (prfA* mutants) that result in variant PrfA proteins whose function is locked in the intracellular activity state support the theory that PrfA activity is allosterically regulated (16,28,37,40,44,47). These prfA* mu-tants constitutively express levels of the actin-nucleating protein ActA comparable to those observed when bacteria are in the host cytosol (40).…”
mentioning
confidence: 87%
“…The interaction of PrfA with cofactors that modulate its activity is suggested by the existence of mutants generated by single amino acid exchanges at different positions in the PrfA protein which lead to permanently active PrfA proteins (termed PrfA*) that are no longer subject to modulation by environmental conditions (Mueller & Freitag, 2005;Ripio et al, 1997;Shetron-Rama et al, 2003;Vega et al, 1998Vega et al, , 2004Wong & Freitag, 2004). Based on this finding and the structural similarity between PrfA and Crp (Lampidis et al, 1994), it has been postulated that wild-type PrfA may be activated by (a) component(s) in a way similar to that by which the PrfA-related Crp (or CAP) factor of E. coli is activated by cAMP (Eiting et al, 2005;Kreft & Vázquez-Boland, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…4). These results indicate apparent activation of plcB and hly by the M7 PrfA due to G145S substitution (Ripio et al, 1997;Vega et al, 2004;Wong & Freitag, 2004). At similar inoculum levels in mice simultaneously infected with the two competition strains, the M7 load in liver samples was about 19.1 and 0.2 % of the total bacterial counts at 48 and 72 h pi, respectively, far less than the EGDe strain (Pv0.01) (Fig.…”
Section: Prfa Of the Low-virulence Strain M7 Was Constitutively Activmentioning
confidence: 82%
“…(Bruno & Freitag, 2010). However, the relationship between virulence and PrfA activation remains unclear (Lauer et al, 2008;Ripio et al, 1997;Vega et al, 2004;Wong & Freitag, 2004). Glomski et al (2003) demonstrated that mutants failing to compartmentalize LLO activities were cytotoxic and of low virulence.…”
Section: Defects Of the M7 Strain In Virulence-related Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation